Kindergarten Resource Pack Mathematics Term -1 - The city school (Lahore The city school)
The Mathematics book for Kindergarten in The City School curriculum introduces foundational math concepts in a fun and engaging way. It covers basic skills like counting, shapes, patterns, and number recognition through hands-on activities and visual aids. The book promotes problem-solving and logical thinking in young learners. It aims to develop early numeracy skills in a playful, interactive environment.
The Mathematics book for Kindergarten in The City School curriculum introduces foundational math concepts in a fun and engaging way. It covers basic skills like counting, shapes, patterns, and number recognition through hands-on activities and visual aids. The book promotes problem-solving and logical thinking in young learners. It aims to develop early numeracy skills in a playful, interactive environment.